The Exchange Rate in the Presence of Transaction Costs: Implications for Tests of Purchasing Power Parity - SERCU, PIET; UPPAL, RAMAN; VAN HULLE, CYNTHIA (Journal of Finance, 1995)
ABSTRACT With transaction costs for trading goods, the nominal exchange rate moves within a band around the nominal purchasing power parity (PPP) value. We model the behavior of the band and of the exchange rate within the band. The model explains why there are below‐unity slope coefficients in regression tests of PPP, and why these increase toward unity under hyperinflation or with low‐frequency data. Our results are independent of the presence of nontraded goods in the economy.